The UNHCR and Disaster Displacement in the 21st Century An Organizational Analysis - Hantscher, Sinja; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book offers an in-depth case study on the leading international refugee agency, the United Nations High Commissioner for Refugees (UNHCR), and its approach to environmentally displaced persons. The author examines the UNHCR on the basis of expert interviews and content analysis in order to highlight why and how the organization is addressing the issue. The analysis draws on organizational as well as security theory, offering readers a better understanding of the connection between the two. The book appeals to scholars in the fields of migration and organizational studies, as well as policymakers and professionals working in international organizations. .
Introduction: Disaster Displacement -- Environmental Changes and the Competing Perspectives on Environmentally Displaced Persons -- Theoretical Background: Organizational Theories and the Research on International Organizations -- Research Design: Operationalizing Security Theory and Organizational Theory -- The UNHCR and Environmentally Displaced Persons -- Conclusion: Putting the UNHCR's EDP-Approach into Context. .
Keywords: Emigration and immigration; International organization; Climatology; Security, International; Human rights; Human Migration; International Organization; Climate Sciences; International Security Studies; Human Rights